PENGARUH KEMUDAHAN PENGGUNAAN TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE TIKTOKSHOP - Rival, Rivaldi saputra; Ramayani Yusuf; Rohimat Nur Hasan (Jurnal Manajemen dan Pemasaran, 2023)
The research entitled The Effect of Ease of Use on Purchase Decisions on Tiktokshop E-Commerce is the result of quantitative research that aims to answer questions about the effect of various ease of use on purchasing decisions on the Tiktok shop application. The research methodology used is quantitative research using survey methods. sampling technique using google form with 100 respondents. data collection technique used a questionnaire which was processed using IBM SPSS 26. Data analysis used multiple linear regression. The results of the study show that the ease of use of the site has a partial effect on purchasing decisions in the TikTok Shop application. Research shows that customer expectations on the TikTok Shop application are valid and significant for purchase decisions and customer satisfaction.